Non-Planar MOSFET Modeling with Analytical Approach - Munawar A Riyadi; Darjat Darjat; Teguh Prakoso; Jatmiko E. Suseno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Non-planar structures have been identified as promising structure for next device generation in the nanoelectronic era. However, the continuous device dimension scaling into nano regime eventually requires more sophisticated model due to the limitation of the existing models. A model for non-planar MOSFET structure was elaborated in this paper, especially for device with pillar structure, using analytical approach. The concern of channel shape and structure were discussed as well. The result shows the shift in subthreshold characteristic in the channel with recessed channel model. The charge sharing is suspected as one of the key parameter in the shift of performance in the recessed region.